Roles of Membrane and Vesicular Traffic in Regulation of the Hippo Pathway - Verghese, Shilpi; Moberg, Ken (Frontiers in Cell and Developmental Biology, 2020)
The Hippo pathway is a well conserved signaling cascade that modulates cell proliferation and survival in response to external cues such as cell:cell contact, injury, and nutritional status. Models of the Hippo pathway have evolved from a series of genetic interactions defined in the fruit fly Drosophila melanogaster into a complex series of biochemical mechanisms in which transmembrane and cytoskeletal proteins modulate cytoplasmic phosphatase and kinase activities that converge on the serine/threonine kinase Warts (Wts) to regulate nuclear entry of the co-activator protein Yorkie (Yki; vertebrate Yap1). This pathway is well conserved in human cells and broadly implicated in cancer. Progress in understanding biochemical events within the Hippo pathway highlights a need for improved understanding of the cell biological contexts in which these molecular interactions occur. A significant body of data linking Hippo signaling to membranes and proteins involved in intracellular membrane trafficking raise the possibility that some molecular regulatory events occur on the cytoplasmic face of vesicles. In Drosophila, a Yki-vesicle link was solidified by discoveries that cytoplasmic Yki concentrates at late-endosomes and physically interacts with two endosomal adaptor proteins, Myopic (Mop) and Leash. These two proteins are required for Yki to transit the endolysosomal pathway and be turned over in lysosomes. Molecules involved in recruiting and tethering Yki along this endosomal route are not defined but are predicted to play key roles in regulating Yki levels and thus Hippo-responsiveness of cells. As Wts is recruited to the apical membrane by upstream Hippo components, endosomal internalization could also affect complexes involved in Yki phosphorylation events that alter nucleocytoplasmic shuttling. Recent work has revealed an unexpected, non-transcriptional role of membrane-associated Yki in triggering actinomyosin contractility via the myosin-regulatory light chain Spaghetti squash (Sqh). How Yki interacts with the membrane and controls Sqh is unclear, but this mechanism represents a novel regulatory mechanism based on induced localization of Yki to a specific membrane compartment. These and other data will be discussed as we review data linking Yki to membrane and vesicular traffic in development and homeostasis and speculate on missing elements of these membrane-linked Yki regulatory mechanisms.